Determinants of business to business e-commerce adoption among public-listed companies in Saudi Arabia - Alhijris, Ali Abdullah A. (2013)
This study investigates the factors that influence B2B e-commerce adoption among public listed companies in Saudi Arabia and determines the key organizational and technological issues that facilitate or hinder e-commerce adoption among these companies. It is also intended in the study to develop a theoretical framework which can help to understand and interpret B2B e-commerce adoption among public listed companies in Saudi Arabia. The study aims to identify a comprehensive set of determinants that influence Saudi companies e-commerce adoption. A questionnaire was used to collect data by means of personal interview with the companies. The final samples were able to be collected from 91 public listed companies, representing 62 percent of all Saudi companies listed in 2012. The main findings of this study reveal that innovation characteristics, context factors, communications factors, and organizational culture factors play a significant role in influencing e-commerce adoption among the companies. A surprising finding was that environmental factors has negatively affected B2B Adoption of E-commerce. However, a closer examination on the study managed to explain this phenomena. This negative direct effect was actually found to be off-setted by the indirect positive effect of environmental factors on B2B e-commerce adoption. Therefore, the environmental factors has indeed indirectly affected the adoption of B2B e-commerce by Saudi companies through its effect on the organizational culture. This study has several limitations. First, since the data set is cross-sectional in nature, this research can only show associations among the variables but cannot be used to analyze longitudinal processes, such as e-commerce functional evolution or its impact on business in a dynamic context. Second, this study has only focused on companies in Saudi Arabia, which may not be the same with public listed companies from other Arab countries. Future research direction would be to expand this study into other countries, such as other Gulf Cooperation Council (GCC) states, to enable generalization of the finding be made on companies in the whole Arab world .